Arthropod diversity in constructed wetlands is affected strongly by shoreline properties but only weakly by grazing - David Åhlén; Jerker Jarsjö; Mats Jonsell; Björn K. Klatt; Lea D. Schneider; John Strand; Peter A. Hambäck (Journal of Biogeography, 2024)
Aim Aquatic‐terrestrial transition zones contain features essential for many species that often benefit wetland biodiversity. Shallow flood‐zone areas and reed beds are indicative of natural wetland habitats; however, how such features affect the native arthropod biodiversity in constructed wetlands is scarcely investigated. We asked how these shoreline features, as well as wetland shoreline properties and grazing management, influence riparian arthropod diversities and habitat specializations. Location Constructed wetlands, Sweden. Taxa Araneae, Coleoptera, Diptera. Methods Taxonomic‐, phylogenetic‐ and trait diversities, along with habitat specialist species richness, were measured in riparian spiders, beetles and selected Diptera in 68 constructed wetlands in two regions of Sweden. We ran structural equation models to estimate direct and indirect effects from shoreline slope, flooded grassland, reed areas and grazing management on group diversities, and used multivariate models to determine drivers on habitat specialist species richness. Results Flooded grassland and reed area, along with shoreline slope influenced arthropod diversities, and responses differed between arthropod groups and diversity metrics. Spider trait diversity was greater in wetlands with larger flooded grassland areas, whilst beetle trait diversity was reduced. Spider phylogenetic diversity was greater in wetlands containing larger reed areas and in wetlands with steeper shorelines. However, species richness in predatory flies was greater in wetlands with more gentle shorelines. Grazing management had limited effects on arthropod diversities; however, species richness in wetland specialist and generalist predatory dipterans was greater in the absence of grazers in wetlands with greater flooded grassland areas. Main Conclusions As requirements vary considerably among arthropods, care must be taken when constructing and managing wetlands to benefit arthropod biodiversity. The present results suggest wetlands with a varied shoreline, albeit with greater proportions of flood areas, or multiple adjacent wetlands with varying shores in a wet landscape and a mild grazing regiment, would accommodate a more diverse arthropod fauna.

Tracking rapid ice recession in a major Southern Alps valley during the last glacial termination - Peter D. Strand; Aaron E. Putnam; Joerg M. Schaefer; George H. Denton; David J.A. Barrell (Quaternary Science Reviews, 2024)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Genetic structure along the strandline: Unravelling invasion history in a one‐dimensional system - Sara Ohadi; Peter K. Ades; Rebecca Ford; Allan E. Strand; Josquin Tibbits; Mohsen B. Mesgaran; Roger D. Cousens (Journal of Biogeography, 2016)
Aim To unravel the genetic processes involved in a case of invasion by one species, the self‐incompatible Cakile maritima Scop. (Brassicaceae) in Australia, as it has replaced a related prior invader, Cakile edentula (Bigelow) Hook. Location Southern and eastern coastlines of Australia. Methods Genetic diversity within and between populations was characterized at a continental scale using microsatellite ( SSR ) markers to examine nuclear diversity and cleaved amplified polymorphic sequence ( CAPS ) markers to examine chloroplasts. DNA was sourced from 24 populations of C. maritima along its putative invasion trajectory and, for comparison, from four populations of C. edentula that are currently being invaded by C. maritima . Analysis of Molecular Variance and a Bayesian assignment method were used to explore the data. Results No evidence was found for progressive loss of diversity in C. maritima in the putative direction of range expansion. Western and south‐eastern populations of C. maritima have almost certainly resulted from independent introductions, although there is evidence of very limited gene flow from west to east. There was considerably greater, spatially structured variation in the south‐east, suggesting multiple introductions of C. maritima to that region. We found evidence of hybridization and introgression from C. edentula into C. maritima , both in the two regions where they are currently sympatric and elsewhere. Main conclusions The invasion history of a species spreading in a largely one‐dimensional habitat can still be highly complex and difficult to interpret. Regional patterns of variation in C. maritima indicate several introductions from different parts of the native range, limited gene flow from the first introduction eastwards and genetic drift within Western Australia. There has also been bi‐directional gene flow between this species and C. edentula . The significance of the introgression from C. edentula into C. maritima with respect to natural selection, however, remains to be determined.